The Impact of the Foreign Currency Selling Window on the Money Supply in Iraq for the Period (2004-2016) - Alaa Mahdi Hadi; Ali Hussein Salman; Amal Abdul Hassan Kazem (Peerian Journals Publishing, 2023)
The transition situation experienced by the Iraqi economy after 2003, and the shift in the trends of monetary policy recently after the Central Bank obtained independence based on Law 56 of 2004, Led to the use of monetary authority modern tools and commensurate with the requirements of orientation towards the market system on the one hand, and the specificity that characterizes the Iraqi economy in light of the structural imbalance suffered by the failure of the financial system and banking on the other, As the Monetary Authority succeeded through the use of the window to sell the currency to control the supply of money and reduce the gap between the exchange rate and the official parallel price, and thus stability of prices and purchasing power in the Iraqi economy.
Keywords: Cash; Foreign currency selling window